2017
DOI: 10.1002/mnfr.201600797
|View full text |Cite
|
Sign up to set email alerts
|

Aged garlic extract suppresses the increase of plasma glycated albumin level and enhances the AMP‐activated protein kinase in adipose tissue in TSOD mice

Abstract: AGE treatment suppresses the increase of plasma glycated albumin level in TSOD mice and this effect is accompanied by the activation of AMPK in adipose tissue, and suggests that AGE may play a potential role in the prevention and treatment of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Basic experiments have also studied the possible mechanisms of how allium vegetables improve metabolic, cardiovascular, and inflammatory outcomes. Animal studies confirmed that aged garlic extract could suppress the increase in plasma glycated albumin levels in spontaneous type 2 diabetes mouse models, and this effect might be partly explained by the activation of AMP‐activated protein kinase followed by the suppression of free fatty acid production and MCP1 gene expression in adipose tissue (Miki et al, ). In Sprague‐Dawley rats fed a high‐fat diet, oral administration of garlic and onion oil suppressed the high‐fat diet‐induced body weight gain, decreased the serum levels of TGs, TC, and LDL, and increased the level of HDL (Yang et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Basic experiments have also studied the possible mechanisms of how allium vegetables improve metabolic, cardiovascular, and inflammatory outcomes. Animal studies confirmed that aged garlic extract could suppress the increase in plasma glycated albumin levels in spontaneous type 2 diabetes mouse models, and this effect might be partly explained by the activation of AMP‐activated protein kinase followed by the suppression of free fatty acid production and MCP1 gene expression in adipose tissue (Miki et al, ). In Sprague‐Dawley rats fed a high‐fat diet, oral administration of garlic and onion oil suppressed the high‐fat diet‐induced body weight gain, decreased the serum levels of TGs, TC, and LDL, and increased the level of HDL (Yang et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…These ndings suggested that anti-atherosclerotic effect of AGE may be attributable to its ability to protect and maintain the vascular endothelial barrier function. AGE has been reported to exert various pharmacological effects, such as anti-atherosclerotic [20,[22][23][24], anti-hypertensive [25,26] and anti-in ammatory effects [20,21], which are considered to be attributable to its sulfur-containing constituents. Therefore, we investigated whether S1PC, SAC and SAMC, three major sulfur-containing constituents in AGE, affect the endothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Aged garlic extract (AGE) is a unique garlic preparation that is produced by aging of raw garlic in an aqueous ethanol solution for more than 10 months. AGE has been shown to exert various biological and pharmacological activities such as anti-in ammatory [20,21], anti-atherosclerotic [20,[22][23][24], antihypertensive [25,26] and anti-oxidative effects [27,28]. In particular, AGE prevented progression of cardiovascular diseases through the improvement of vascular endothelial dysfunction in clinical studies [24,26,[29][30][31][32].…”
mentioning
confidence: 99%
“…Aged garlic extract (AGE) is produced by extracting and aging garlic slices in an aqueous ethanol solution for >10 months and has been shown to modulate several immune functions, such as decreasing inflammatory cytokines and chemokines in animal models (1)(2)(3)(4). In addition, the supplementation of AGE was previously shown to increase the numbers of γδ-T and natural killer (NK) cells, and to reduce the levels of inflammatory cytokines, such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α, in a clinical study (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the supplementation of AGE was previously shown to increase the numbers of γδ-T and natural killer (NK) cells, and to reduce the levels of inflammatory cytokines, such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α, in a clinical study (5). AGE has been shown to exert immuno-enhancing and anti-inflammatory effects (1)(2)(3)(4)(5). S-1-propenylcysteine (S1PC), a major characteristic sulfur compound in AGE, which exhibits good oral bioavailability in rats and canines (6), has been shown to exert several beneficial effects, such as immunoregulatory, anti-hypertensive and blood flow-promoting effects (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%